2015
DOI: 10.1002/2014jd022977
|View full text |Cite
|
Sign up to set email alerts
|

Impact of snow darkening via dust, black carbon, and organic carbon on boreal spring climate in the Earth system

Abstract: Dust, black carbon (BC), and organic carbon (OC) aerosols, when deposited onto snow, are known to reduce the albedo of the snow (i.e., snow darkening effect (SDE)). Here using the NASA Goddard Earth Observing System Model, Version 5 (GEOS-5) with aerosol tracers and a state-of-the-art snow darkening module (GOddard SnoW Impurity Module: GOSWIM) for the land surface, we examine the role of SDE on climate in the boreal spring snowmelt season. SDE is found to produce significant surface warming (over 15 W m À2) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
98
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 131 publications
(374 reference statements)
2
98
0
Order By: Relevance
“…Another important factor is the light-absorbing aerosols (LAAs, e.g., black carbon (BC), organic carbon (OC), and dust) in snow (e.g., Flanner et al, 2007; et Qian et al, 2015;Yasunari et al, 2015). Previous studies have shown that LAAs in snow can significantly reduce the surface albedo (often known as the snow darkening effect; SDE), modify the surface energy budget and snowmelt, and lead to the modification of hydrologic cycles (e.g., Warren and Wiscombe, 1980;Hansen and Nazarenko, 2004;Flanner et al, 2007Flanner et al, , 2009Painter et al, 2007Painter et al, , 2010Qian et al, 2009Qian et al, , 2011Yasunari et al, 2015). Moreover, the LAA-induced snow albedo reduction may initiate positive feedback processes, which can amplify the reduction of snowpack (e.g., Flanner et al, 2009;Qian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another important factor is the light-absorbing aerosols (LAAs, e.g., black carbon (BC), organic carbon (OC), and dust) in snow (e.g., Flanner et al, 2007; et Qian et al, 2015;Yasunari et al, 2015). Previous studies have shown that LAAs in snow can significantly reduce the surface albedo (often known as the snow darkening effect; SDE), modify the surface energy budget and snowmelt, and lead to the modification of hydrologic cycles (e.g., Warren and Wiscombe, 1980;Hansen and Nazarenko, 2004;Flanner et al, 2007Flanner et al, , 2009Painter et al, 2007Painter et al, , 2010Qian et al, 2009Qian et al, , 2011Yasunari et al, 2015). Moreover, the LAA-induced snow albedo reduction may initiate positive feedback processes, which can amplify the reduction of snowpack (e.g., Flanner et al, 2009;Qian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In past decades modeling studies have been undertaken to quantify the impacts of SDE by LAAs (e.g., Flanner et al, 2007;Qian et al, 2009;Oaida et al, 2015;Yasunari et al, 2015). Generally the models developed have the ability to simulate the temporal evolution of snow albedo under the influence of LAAs in snow.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations